Sports innovation in the journey towards rowing gold: enhancement of performance and well being - McGregor, A. H. (Sports innovation, technology and research, 2016)
The Olympic Games is considered to be the ultimate international sporting event, where elite athletes across the globe compete, and the margins between success and failure have become increasingly small. In the UK, rowing has over the years been one of our most successful sports with medal success and world rankings increasing significantly in the last decade. The recent success at the London 2012 games also saw a rise in participation in the sport with over 32,000 people signing up for rowing courses in the UK and 1,000 new applicants to GB Rowing's START talent ID programme which is seen as a gateway to elite performance…